16.5k views
0 votes
I would appreciate help,i dont need an explanation, just the answers. thankyou

I would appreciate help,i dont need an explanation, just the answers. thankyou-example-1
User Tuxtimo
by
4.5k points

1 Answer

2 votes

we have

f(x)=7x-1

g(x)=(1/7)(x+1)

Part 1

Find out (fog)(x)

(fog)(x)=f(g(x))=7(1/7)(x+1)-1=x+1-1=x

therefore

(fog)(x)=x

Part 2

Find out (gof)(x)

(gof)(x)=g(f(x))=(1/7)(7x-1+1)=x

therefore

(gof)(x)=x

Part 3

(fog)(x)=(gof)(x)=x

the answer is Yes

User Roman Klimenko
by
5.4k points